2017
DOI: 10.3390/agriculture7010004
|View full text |Cite
|
Sign up to set email alerts
|

Practices for Reducing Greenhouse Gas Emissions from Rice Production in Northeast Thailand

Abstract: Land management practices for rice productivity and carbon storage have been a key focus of research leading to opportunities for substantial greenhouse gas (GHG) mitigation. The effects of land management practices on global warming potential (GWP) and greenhouse gas intensity (GHGI) from rice production within the farm gate were investigated. For the 13 study sites, soil samples were collected by the Land Development Department in 2004. In 2014, at these same sites, soil samples were collected again to estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 52 publications
(41 reference statements)
0
12
0
Order By: Relevance
“…N 2 O emissions contribute much less than CH 4 emissions to the global warming potential in Indonesia, 43 Japan, 19,44 California, 45 the Philippines 22 and Uruguay 46 . In northeast Thailand, Arunrat and Pumijumnong 47 reported that the contribution of CH 4 (88%) to net GWP is much higher than those of N 2 O (8%) and CO 2 (4%) in rice production. Therefore, reducing CH 4 emissions from rice soil is the most effective way to mitigate the total global warming potential from rice production.…”
Section: Discussionmentioning
confidence: 99%
“…N 2 O emissions contribute much less than CH 4 emissions to the global warming potential in Indonesia, 43 Japan, 19,44 California, 45 the Philippines 22 and Uruguay 46 . In northeast Thailand, Arunrat and Pumijumnong 47 reported that the contribution of CH 4 (88%) to net GWP is much higher than those of N 2 O (8%) and CO 2 (4%) in rice production. Therefore, reducing CH 4 emissions from rice soil is the most effective way to mitigate the total global warming potential from rice production.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the nutrient omission response to the soil when in standing water disappears from the paddies. However, submerge conditions lead to chemical changes that noticeably stimulate SOC dynamics under O 2 limited conditions [19,104]. Via many processes of an oxidation-reduction reaction, SOC dynamics change soil pH, reduction of C, nitrogen (N), sulfur (S), and redox potential in a waterlogged rice field [105].…”
Section: Influence Of Management Practices On Soil Organic Carbon Andmentioning
confidence: 99%
“…Soil organic carbon (SOC) storage is the key function of agricultural soil, as it interacts with other functions, e.g., soil fertility, nutrient cycling, temperature, and pH balance (Lal et al, 2007;Six et al, 2002). It is also related to sustainable strategies to mitigate the emission of greenhouse gases (GHGs) (Arunrat and Pumijumnong, 2017;Rajan et al, 2017). Increasing SOC content by 1 g kg -1 can increase rice yield by 302 kg ha -1 (Arunrat et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%